Corrigendum to “A Comparison of SWAT Model Calibration Techniques for Hydrological Modeling in the Ganga River Watershed” [Engineering 4 (2018) 643–652] (Engineering (2018) 4(5) (643–652), (S2095809917306586), (10.1016/j.eng.2018.08.012)) - Shivhare N.; Kumar Singh Dikshit P.; Bihari S. (My University, 2025)
The authors regret to inform that several numbers are mistaken due to clerical errors. 1. In the last paragraph of Section 1, The “Section 4.2.” in the sentence “By analyzing the results, assumptions, and limitations of these calibration techniques, the best technique among the three was determined based on five categories, as described in Section 4.2.” should be changed to “Section 5.2”. 2. In Section 4.6, “In this step, using the soil map, user soil table, LULC map, and slope map (Fig. 4) of the study area, the watershed was divided into 160 HRUs.”, where “160 HRUs” should be changed to “760 HRUs”. The authors would like to apologize for any inconvenience caused. © 2019